KETAHANAN RUMAH TANGGA MAHASISWA BERKELUARGA: STUDI FENOMENOLOGIS DAN ANALISIS MAQĀṢID SHARĪ’AHDI STDI IMAM SYAFI’I JEMBER - Nur Baiti Hidayah; Muhammad Zakki; Nelud Darajaatul Aliyah (LPPM STAI Muhammadiyah Probolinggo, 2026)
Marriage is a solemn act of worship for the perfection of religion, as is education in Islamic law. Combining these two acts of worship is not easy; in fact, it is fraught with challenges. This study aims to identify the factors of resilience in the households of married students at STDI Imam Syafi'i Jember and their relevance to the values of maqāṣid sharī'ah. This study is a qualitative study with a phenomenological approach, which is an approach to reveal the phenomena experienced by a group of individuals clearly. The results of this study found that there are two types of household resilience factors, namely positive factors, such as piety to Allah Ta'ala, open communication, ability in time and role management, sufficient economy, and commitment to study in Jember. Then there are negative factors, such as difficulties in time management, difficulties in earning a living, difficulties in managing emotions, and intervention from the extended family. These factors are closely related to the core values of maqāṣid sharī’ah: hifz al-dīn, hifz al-nafs, hifz al-nasl, hifz al-‘aql, and hifz al-māl. This study is expected to provide a deep understanding of the concept of maqāṣid sharī’ah in the context of household resilience and harmony.